2015
DOI: 10.1007/s11085-015-9543-6
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Behavior and Mechanism of Inconel 740H Alloy for Advanced Ultra-supercritical Power Plants Between 1050 and 1170 °C

Abstract: The oxidation behavior and mechanism of as-cast Inconel 740H superalloy, newly developed for advanced ultra-supercritical power plants superheater and reheater pipes, were investigated in the temperature range of 1050-1170°C in air. Isothermal oxidation testing, X-ray diffraction, scanning electron microscopy and energy dispersive X-ray spectroscopy were used in this study. The results showed that the oxidation of Inconel 740H was a diffusion-controlled process and controlled by the outward diffusion of metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Literature data [ 22 , 23 ] suggest that TiO 2 oxides form at the beginning of oxidation (before Cr 2 O 3 oxide). However, the higher Cr content in the chemical composition of the superalloy caused significant growth and dominance of Cr 2 O 3 oxide on the superalloy surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature data [ 22 , 23 ] suggest that TiO 2 oxides form at the beginning of oxidation (before Cr 2 O 3 oxide). However, the higher Cr content in the chemical composition of the superalloy caused significant growth and dominance of Cr 2 O 3 oxide on the superalloy surface.…”
Section: Resultsmentioning
confidence: 99%
“…The investigations of the superalloy surface after 1000 h showed that the outer part of the external oxide layer was TiO 2 oxide crystallites, which grew with time ( Figure 5 d,e). The formation of TiO 2 at the steam-oxide layer border resulted from the easy diffusion of Ti ions through the Cr 2 O 3 layer [ 22 , 23 ]. Moreover, evaluation of the chemical analysis of the external oxide layer also revealed diffusion of Mn, whose beginning started earlier, i.e., after 1000 h of oxidation ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be mentioned, that materials dedicated to the superheater/reheater should have an outstanding oxidation resistance. According to the literature, 60% of boiler failures occurred due to the steam oxidation and coal-ash corrosion [5]. Among the main reasons of the nickel-based alloys failure due to a high temperature corrosion, one can indicate a loss of the surface strength, crack initiation, dealloying and component failure [6].…”
Section: Introductionmentioning
confidence: 99%
“…Among the main reasons of the nickel-based alloys failure due to a high temperature corrosion, one can indicate a loss of the surface strength, crack initiation, dealloying and component failure [6]. Such mechanisms are associated with the occurrence of specific oxides: Cr 2 O 3 , NiCr 2 O 4 , and NiFe 2 O 4 (Inconel 718) [7], Cr 2 O 3 and NiCr 2 O 4 (Inconel 625) [8], NiCr 2 O 4 , Cr 2 O 3 and TiO 2 (Inconel 625 [9] and Inconel 740H [10]). However, the oxidation behaviour and its mechanism for the nitrided Inconel 740H nickel alloy at 1000 °C were not investigated as yet.…”
Section: Introductionmentioning
confidence: 99%